laminate
A laminate with a resin layer made from a thermosetting composition containing alicyclic epoxy compounds addresses peeling issues by controlling metal diffusion, enhancing adhesive strength and reliability in high-temperature conditions.
Patent Information
- Application Number
- JP2024060163
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-12
- Filing Date
- 2024-04-03
- Publication Date
- 2024-12-24
AI Technical Summary
Existing semiconductor power packages face issues with peeling between the resin layer and metal members under high-temperature conditions, leading to a decline in thermal and electrical properties, and long-term reliability is not adequately maintained due to metal diffusion into the resin layer.
A laminate comprising a metal member and a resin layer, where the resin layer is a cured product of a thermosetting composition containing a thermosetting compound with an alicyclic epoxy group, with controlled metal content near the interface to suppress diffusion and maintain adhesive strength.
The laminate achieves high adhesive strength and suppresses peeling between the resin layer and metal member in high-temperature environments, ensuring long-term reliability and suitability for automotive applications.
Smart Images

Figure 2024178102000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate. [Background technology]
[0002] Semiconductor power packages and power modules are constructed by joining or adhering multiple components made of different materials, such as metal frames, semiconductor chips, die bond materials, bonding wires, and sealing resin (mold resin). The sealing resin of semiconductor packages is required to have heat resistance at the solder reflow temperature (260°C) during solder mounting. Thermosetting resins have traditionally been used as sealing resins with high heat resistance. In general, epoxy resins made from bisphenol A have been widely used.
[0003] In addition, the sealing resin is used to protect the inside from the external environment. For example, when peeling occurs at the interface between the metal frame and the sealing resin, cracks may develop from the peeled portion to the joint with the die bond material, resulting in a decrease in the thermal and electrical properties of the semiconductor chip. Therefore, the adhesion between the metal frame, which has the largest adhesion area, and the sealing resin is particularly important. There is a demand for a highly reliable laminate in which peeling does not occur between the resin layer and the metal member under the usage environment. Furthermore, in recent years, with the application of semiconductor packages to automobile parts, there is a demand for high reliability under high temperature conditions exceeding 200°C, temperature cycle conditions of -55°C to 175°C, high temperature and high humidity conditions (121°C, 100% RH, 2 atm), etc.
[0004] For example, a resin that has a linear expansion coefficient similar to that of metal (e.g., copper) and a glass transition temperature exceeding 200° C. has been developed as a sealing resin that is prevented from peeling off from a metal member. In addition, in order to achieve a linear expansion coefficient close to that of a metal member, about 70 to 80% of silica filler is blended into the sealing resin. However, even if such a resin is used, peeling off from the metal member cannot be completely prevented under the above-mentioned high temperature conditions, and there is a problem that long-term reliability cannot be obtained, and the mechanism behind this has not yet been elucidated.
[0005] Non-Patent Document 1 reports on metal diffusion into polymers such as polyimide resin and polycarbonate resin. Non-Patent Document 2 describes that when copper comes into contact with resin, metal ions act as a catalyst to promote the autoxidation reaction of the polymer, causing the polymer to deteriorate. Non-Patent Document 3 shows the results that mixing copper with epoxy resin accelerates the deterioration of the epoxy resin at high temperatures. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Franz Faupel, Ralf Willecke, Axel Thran, Materials Science and Engineering, R22(l998) 1-55 [Non-Patent Document 2] Yoshito Ohtake, Heating, Air-Conditioning and Sanitary Engineering 80 (1), 69-75 (2006) [Non-Patent Document 3] Hong, SG, & Wang, TC, Journal of applied polymer science, 52(9), 1339-1351 (1994) Summary of the Invention [Problem to be solved by the invention]
[0007] A laminate in which the adhesive strength between the resin layer and the metal member is high, the initial adhesive strength is maintained in a high-temperature environment, and peeling at the interface with the metal member is suppressed has not yet been proposed. An object of the present disclosure is to provide a laminate having long-term reliability in a high-temperature environment. [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have focused on the fact that metal elements originating from a metal member diffuse into a resin layer in a high-temperature environment, and have found that the decrease in adhesive strength can be suppressed by controlling the metal concentration in the resin in the immediate vicinity of the contact interface with the metal member, thereby solving the above-mentioned problem.
[0009] That is, the laminate of the present disclosure includes a metal member and a resin layer laminated on the metal member. The resin layer is a cured product of a thermosetting composition. The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group. The metal content of the resin layer after 1000 hours at 200°C, as determined by the following measurement method, is 1 atomic% or less at a depth of 100 nm from the contact surface with the metal member. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction on the resin layer peeled off from the metal member using an X-ray photoelectron spectroscopy device (XPS) to measure the number of atoms of metal elements, carbon and oxygen, and the ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).)
[0010] From another viewpoint, the present disclosure relates to a thermosetting composition for producing the laminate. The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group. The cured product of the thermosetting composition has a chlorine content of 1000 ppm or less and a sulfur content of 1000 ppm or less. The cured product of the thermosetting composition has a metal content of 1 atomic % or less at a depth of 100 nm from the contact surface with a metal member after 1000 hours at 200°C, as measured by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) made of a cured product of a thermosetting composition laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction of the resin layer peeled off from the metal member using an X-ray photoelectron spectrometer (XPS) to measure the number of atoms of metal elements, carbon and oxygen, and the ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).) Effect of the Invention
[0011] According to the present disclosure, a laminate having high adhesive strength between a metal member and a resin layer can be obtained. With this laminate, peeling at the interface between the metal member and the resin layer is suppressed even in a high-temperature environment, so that the performance can be maintained for a long period of time. The laminate of the present disclosure can also be suitably used for automobile parts that require heat resistance to high temperatures. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1A is an XPS profile of Example 1 before the high-temperature treatment, and FIG. 1B is an XPS profile of Example 1 after the high-temperature treatment. [Diagram 2] FIG. 2A is an XPS profile of Example 2 before the high-temperature treatment, and FIG. 2B is an XPS profile of Example 2 after the high-temperature treatment. [Diagram 3] FIG. 3A is an XPS profile of Comparative Example 1 before the high-temperature treatment, and FIG. 3B is an XPS profile of Comparative Example 1 after the high-temperature treatment. [Figure 4] FIG. 4A is an XPS profile of Reference Example 1 before the high-temperature treatment, and FIG. 4B is an XPS profile of Reference Example 1 after the high-temperature treatment. [Diagram 5] FIG. 5 is an infrared absorption spectrum obtained for Example 1. [Figure 6] FIG. 6 is an infrared absorption spectrum obtained for Example 2. [Figure 7] FIG. 7 is an infrared absorption spectrum obtained for Comparative Example 1. [Figure 8] FIG. 8 is an infrared absorption spectrum obtained for Reference Example 1. [Figure 9] FIG. 9 shows cross-sectional images of Comparative Example 1 after high temperature treatment, where FIGS. 9A and 9B are TEM images, and FIGS. 9C to 9E are EDS images. [Figure 10] FIG. 10 shows cross-sectional images of Comparative Example 2 after high-temperature treatment, where FIG. 10A is a TEM image and FIGS. 10B-C are EDS images. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] An example of a preferred embodiment will be specifically described below. Each configuration and their combination in each embodiment is an example, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the present disclosure. The present disclosure is not limited by the embodiments, but only by the scope of the claims. In addition, each aspect disclosed in this specification can be combined with any other feature disclosed in this specification.
[0014] In the present specification, the range "X to Y" means "X or more and Y or less." Furthermore, unless otherwise noted, all test temperatures were room temperature (20°C ± 5°C).
[0015] (Laminate) The laminate of the present disclosure includes a metal member and a resin layer laminated on the metal member. The resin layer is a cured product of a thermosetting composition. The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group. The metal content of the resin layer after 1000 hours at 200°C, as determined by the following measurement method, is 1 atomic% or less at a depth of 100 nm from the contact surface with the metal member. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction on the resin layer peeled off from the metal member using an X-ray photoelectron spectroscopy device (XPS) to measure the number of atoms of metal elements, carbon and oxygen, and the ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).)
[0016] An increase in the metal content in the resin layer is one of the factors that cause the resin to deteriorate. In particular, deterioration of the resin in the immediate vicinity of the contact surface with the metal member is thought to cause peeling between the resin layer and the metal member. However, according to the laminate of the present disclosure, even when placed in a high-temperature environment for a long period of time, the diffusion of metal elements from the metal member to the resin layer is significantly reduced, and the metal content in the vicinity of the contact surface with the metal member is maintained at 1 atomic% or less. In this laminate, peeling between the resin layer and the metal member in a high-temperature environment can be sufficiently suppressed. This laminate has excellent high-temperature reliability. The laminate of the present disclosure can be applied to semiconductor devices such as power packages and power modules. A semiconductor device including the laminate of the present disclosure has long-term reliability in a high-temperature environment.
[0017] Furthermore, the laminate of the present disclosure has high high-temperature reliability without forming a metal diffusion prevention film between the metal member and the resin layer. In other words, in this laminate, even when the resin layer is laminated in direct contact with the metal member, the diffusion of metal elements from the metal member to the resin layer can be reduced. That is, the laminate of the present disclosure may be composed of a metal member and a resin layer laminated directly on the surface of the metal member.
[0018] From the standpoint of suppressing peeling of the resin layer, the metal content after 1,000 hours at 200°C, as determined by the above measurement method, may be 1 atomic % or less at a depth of 50 nm from the contact surface with the metal member, may be 1 atomic % or less at a depth of 30 nm, or may be 1 atomic % or less at a depth of 10 nm.
[0019] In the laminate of the present disclosure, the adhesiveness between the resin layer and the metal member may be evaluated by shear strength. From the viewpoint of preventing peeling, the shear strength of the resin layer to the metal member is preferably 5 MPa or more, may be 10 MPa or more, or may be 15 MPa or more, and the upper limit is not particularly limited. In this specification, the shear strength is measured at room temperature, at a head speed of 50 μm / s, and at a distance of 200 μm between the head and the metal member. Details of the measurement method will be described in detail in the Examples.
[0020] Furthermore, from the viewpoint of suppressing peeling of the resin layer from the metal member, in the laminate of the present disclosure, the shear strength of the bonding surface between the resin layer and the metal member after storage for 240 hours at a temperature of 200°C is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, and particularly preferably 80% or more, of the shear strength before the storage.
[0021] In a preferred embodiment, the shear strength of the bonding surface between the resin layer and the metal member after storage for 500 hours at a temperature of 200°C is preferably 10% or more, more preferably 25% or more, even more preferably 50% or more, and particularly preferably 80% or more, of the shear strength before storage.
[0022] In another preferred embodiment, the shear strength of the bonding surface between the resin layer and the metal member after storage for 1000 hours at a temperature of 200°C is preferably 5% or more, more preferably 10% or more, even more preferably 20% or more, and particularly preferably 30% or more, of the shear strength before storage.
[0023] (Metal parts) The shape of the metal member may be a plate, a rod, etc. For example, examples of metal members constituting a semiconductor device include substrates, electrodes, wires, etc.
[0024] The material of the metal member may be copper, nickel, silver, etc. Copper is preferable as the material of the constituent member of the semiconductor device. When the material of the metal member is copper, the resin layer contained in the laminate may have a copper content of 1 atomic % or less at a depth of 100 nm from the contact surface with the metal member after 1000 hours at 200°C, as determined by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction on the resin layer peeled off from the metal member using an X-ray photoelectron spectroscopy device (XPS) to measure the number of copper, carbon and oxygen atoms, and the ratio of the number of copper atoms to the total number of carbon, oxygen and copper atoms at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the copper content (atomic %).)
[0025] Furthermore, from the viewpoint of suppressing peeling of the resin layer, the copper content after 1,000 hours at 200°C, as determined by the above measurement method, may be 1 atomic % or less at a depth of 50 nm from the contact surface with the metal member, may be 1 atomic % or less at a depth of 30 nm, or may be 1 atomic % or less at a depth of 10 nm.
[0026] From the viewpoint of adhesion to the resin layer, the surface of the metal member may be intentionally oxidized, or may be unintentionally covered with a natural oxide film.
[0027] (Thermosetting composition) The thermosetting composition of the present disclosure is used to manufacture the laminate described above. In particular, the laminate of the present disclosure is manufactured by laminating a resin layer, which is a cured product of the thermosetting composition of the present disclosure, on a metal member. This metal member may be a component of a semiconductor device. A semiconductor device may be manufactured by laminating a resin layer, which is a cured product of the thermosetting composition of the present disclosure, on a metal member, which is a component of a semiconductor device. In other words, the thermosetting composition of the present disclosure can be used to manufacture a semiconductor device.
[0028] The thermosetting composition of the present disclosure contains a thermosetting compound. In the present disclosure, the thermosetting compound has an alicyclic epoxy group. The thermosetting compound has an alicyclic epoxy group, so that the diffusion of metal elements from the metal member to the resin layer can be suppressed. By using a thermosetting composition containing a thermosetting compound having an alicyclic epoxy group, a laminate having high adhesive strength between the metal member and the resin layer can be obtained. The thermosetting compound may have a plurality of alicyclic epoxy groups. A thermosetting compound having two or more alicyclic epoxy groups is preferred. As long as the effects of the present disclosure can be obtained, the thermosetting compound may have other epoxy groups together with the alicyclic epoxy group. Examples of the other epoxy groups include glycidyl groups. In addition, within the range in which the effects of the present disclosure can be obtained, the thermosetting composition may contain two or more thermosetting compounds having an alicyclic epoxy group, and may contain a thermosetting compound having no alicyclic epoxy group together with a thermosetting compound having an alicyclic epoxy group.
[0029] The thermosetting compound having a plurality of alicyclic epoxy groups may be, for example, a compound represented by the following formula (1). [ka]
[0030] In the above formula (1), X represents a single bond or a linking group. Examples of the linking group include a divalent hydrocarbon group, an alkenylene group in which a part or all of the carbon-carbon double bonds are epoxidized, a carbonyl group (-CO-), an ether bond (-O-), an ester bond (-COO-), a carbonate group (-O-CO-O-), an amide group (-CONH-), and the like. The linking group X may be a functional group in which a plurality of these groups are linked together.
[0031] Examples of the divalent hydrocarbon group include linear or branched alkylene groups having 1 to 18 carbon atoms, and divalent alicyclic hydrocarbon groups having 3 to 18 carbon atoms. Examples of the linear or branched alkylene groups having 1 to 18 carbon atoms include methylene, methylmethylene, dimethylmethylene, ethylene, propylene, and trimethylene. Examples of the divalent alicyclic hydrocarbon groups having 3 to 18 carbon atoms include cycloalkylene groups such as 1,2-cyclopentylene, 1,3-cyclopentylene, 1,2-cyclohexylene, 1,3-cyclohexylene, and 1,4-cyclohexylene.
[0032] Examples of the alkenylene group in the alkenylene group in which some or all of the carbon-carbon double bonds have been epoxidized (hereinafter also referred to as "epoxidized alkenylene group") include linear or branched alkenylene groups having 2 to 8 carbon atoms. Examples of the linear or branched alkenylene group having 2 to 8 carbon atoms include vinylene group, propenylene group, 1-butenylene group, 2-butenylene group, butadienylene group, pentenylene group, hexenylene group, heptenylene group, and octenylene group. The epoxidized alkenylene group is preferably an alkenylene group in which all of the carbon-carbon double bonds have been epoxidized, and more preferably an alkenylene group in which all of the carbon-carbon double bonds have been epoxidized and have 2 to 4 carbon atoms.
[0033] The cyclohexene oxide group (alicyclic epoxy group) in the above formula (1) may have a substituent (for example, an alkyl group having 1 to 10 carbon atoms, etc.) bonded thereto.
[0034] Representative examples of the compound represented by the above formula (1) include compounds in which X in the above formula (1) is a group containing an ester bond, such as (3,4,3',4'-diepoxy)bicyclohexyl and 1,2-epoxy-1,2-bis(3,4-epoxycyclohexan-1-yl)ethane.
[0035] Examples of the compound in which X in the above formula (1) is a group containing an ester bond include compounds represented by the following formulae (1-1) to (1-5). [ka]
[0036] The thermosetting compound preferably contains a saturated or unsaturated cyclic hydrocarbon group. This cyclic hydrocarbon group may contain a heteroatom (e.g., nitrogen (N), sulfur (S), etc.). This cyclic hydrocarbon group is a concept that also includes polycyclic aromatic groups (e.g., naphthalene skeletons) and the like.
[0037] The thermosetting compound preferably has at least one of a five-membered ring and a six-membered ring as a cyclic hydrocarbon group, more preferably has a six-membered ring, and particularly preferably has only a six-membered ring. Examples of the six-membered ring include a benzene skeleton and a cyclohexane skeleton. A six-membered ring that is a cyclohexane skeleton is preferred. The cyclic hydrocarbon group preferably does not contain an aromatic group, and preferably does not contain a heteroatom.
[0038] As long as the effects of the present disclosure can be obtained, the thermosetting compound may further have a hydroxyl group in addition to the alicyclic epoxy group. This hydroxyl group may be an alcoholic hydroxyl group or a phenolic hydroxyl group.
[0039] Preferably, the epoxy equivalent of the thermosetting compound is 200 g / eq or less. Here, "epoxy equivalent" refers to the amount (g) of the thermosetting compound per equivalent of epoxy group. The smaller the epoxy equivalent, the higher the crosslink density of the resulting cured product. It is presumed that the increase in the crosslink density of the cured product suppresses the diffusion of metal elements from the metal member to the resin layer. From the viewpoint of improving high-temperature reliability, the epoxy equivalent of the thermosetting compound is more preferably 180 g / eq or less, further preferably 150 g / eq or less, and particularly preferably 130 g / eq or less. The lower limit of the epoxy equivalent is not particularly limited, but the epoxy equivalent of the thermosetting compound may be 50 g / eq or more. The epoxy equivalent of the thermosetting compound is measured, for example, in accordance with the method described in JIS K7236:2009.
[0040] Preferably, the chlorine content of the thermosetting compound is 1000 ppm or less. According to the findings of the present inventors, the chlorine derived from the thermosetting compound reacts with the metal oxide to ionize the metal. Therefore, the metal becomes easier to move, and the diffusion of the metal element from the metal member to the resin layer is accelerated. From the viewpoint of suppressing the diffusion of the metal element in a high-temperature environment, the chlorine content of the thermosetting compound is more preferably 500 ppm or less, even more preferably 100 ppm or less, particularly preferably less than 10 ppm, and ideally 0. The chlorine content in the thermosetting compound is measured in accordance with the method described in JIS K7243-3:2005.
[0041] The content of the thermosetting compound having an alicyclic epoxy group may be 5% by weight or more, 10% by weight or more, or 15% by weight or more of the entire thermosetting composition. The content of the thermosetting compound having an alicyclic epoxy group may be 50% by weight or less, 40% by weight or less, or 30% by weight or less of the entire thermosetting composition.
[0042] The thermosetting composition may contain a curing agent together with the thermosetting compound. The curing agent may be any compound capable of curing the thermosetting compound, and examples of the curing agent include an acid anhydride curing agent, an amine curing agent, and a phenolic curing agent.
[0043] Examples of the acid anhydride curing agent include phthalic anhydride (formula (2) below), methyltetrahydrophthalic anhydride (e.g., 4-methyltetrahydrophthalic anhydride, 3-methyltetrahydrophthalic anhydride, etc.), methylhexahydrophthalic anhydride (e.g., 4-methylhexahydrophthalic anhydride, 3-methylhexahydrophthalic anhydride, etc.), dodecenyl succinic anhydride, methyl end methylene tetrahydrophthalic anhydride, maleic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylcyclo Examples of such curing agents include hexene dicarboxylic anhydride, pyromellitic anhydride, trimellitic anhydride, benzophenone tetracarboxylic anhydride, nadic anhydride, methyl nadic anhydride, hydrogenated methyl nadic anhydride, 4-(4-methyl-3-pentenyl)tetrahydrophthalic anhydride, succinic anhydride, adipic anhydride, sebacic anhydride, dodecanedioic anhydride, methylcyclohexene tetracarboxylic anhydride, vinyl ether-maleic anhydride copolymer, alkylstyrene-maleic anhydride copolymer, etc. The thermosetting composition may contain two or more of these as a curing agent.
[0044] [ka]
[0045] Examples of the amine-based curing agent include aliphatic polyamines, alicyclic polyamines, aromatic polyamines, etc. Examples of the aliphatic polyamines include ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, polypropylenetriamine, etc. Examples of the alicyclic polyamines include menthenediamine, isophoronediamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, N-aminoethylpiperazine, 3,9-bis(3-aminopropyl)-3,4,8,10-tetraoxaspiro[5,5]undecane, etc. Examples of aromatic polyamines include m-phenylenediamine, p-phenylenediamine, tolylene-2,4-diamine, tolylene-2,6-diamine, mesitylene-2,4-diamine, 3,5-diethyltolylene-2,4-diamine, 3,5-diethyltolylene-2,6-diamine, biphenylenediamine, 4,4-diaminodiphenylmethane, 2,5-naphthylenediamine, and 2,6-naphthylenediamine.
[0046] Examples of phenol-based curing agents include novolac-type phenolic resins, novolac-type cresol resins, p-xylylene-modified phenolic resins, p-xylylene / m-xylylene-modified phenolic resins, terpene-modified phenolic resins, dicyclopentadiene-modified phenolic resins, and triphenolpropane.
[0047] The amount of the curing agent contained in the thermosetting composition can be appropriately adjusted depending on the type of the thermosetting compound. For example, the amount may be 50 parts by weight or more, 60 parts by weight or more, or 70 parts by weight or more, and may be 200 parts by weight or less, or 180 parts by weight or less, relative to 100 parts by weight of the thermosetting compound.
[0048] The thermosetting composition may further contain a filler from the viewpoint of adjusting the molding shrinkage rate, thermal expansion coefficient, thermal conductivity, mechanical strength, etc. of the obtained cured product. Examples of the filler include silica, boron nitride, aluminum nitride, silicon nitride, gallium nitride, alumina, silicon carbide, magnesium oxide, diamond, etc.
[0049] From the viewpoint of adjusting the curability, storage stability, etc., the thermosetting composition may contain a curing accelerator. Examples of the curing accelerator include tetraphenylphosphonium tetraphenylborate, imidazoles, triphenylphosphate (TPP), and amine-based curing accelerators. Examples of the amine-based curing accelerator include boron trifluoride monoethylamine.
[0050] In the present disclosure, the thermosetting composition may be a prepreg. That is, the thermosetting composition may further contain fibers. Examples of the fibers include carbon fibers, glass fibers, aramid fibers, boron fibers, polyparaphenylene benzobis oxazole (PBO) fibers, polyethylene fibers, alumina fibers, and silicon carbide fibers. The fibers may be included in the thermosetting composition in the form of a woven fabric, a nonwoven fabric, or a loose fiber.
[0051] When the thermosetting composition contains a fiber, the fiber may be a monofilament or a multifilament. When the fiber is a monofilament, the fineness of the single fiber is preferably 0.2 to 2.0 dtex, more preferably 0.4 to 1.8 dtex. When the fiber is a multifilament, the number of filaments in the fiber is preferably 2,500 to 50,000.
[0052] From the viewpoint of adjusting releasability, adhesiveness, printability, etc., the thermosetting composition may further contain a release agent. Examples of the release agent include higher fatty acids, higher fatty acid esters, higher fatty acid calcium salts, etc. Specific examples include carnauba wax, polyethylene wax, etc.
[0053] From the viewpoint of reducing stress (reducing elasticity) of the resulting cured product, the thermosetting composition may further contain a modifier (sometimes referred to as a "stress reducing agent"). Examples of the modifier include butadiene-based rubbers and silicone compounds. Examples of butadiene-based rubbers include methyl acrylate-butadiene-styrene copolymers and methyl methacrylate-butadiene-styrene copolymers.
[0054] The thermosetting composition may contain other additives as long as the effects of the present disclosure are obtained. Examples of such additives include flame retardants, pigments, and ion trapping agents.
[0055] Examples of the flame retardant include organic phosphorus compounds, antimony oxide, aluminum hydroxide, magnesium hydroxide, etc. Examples of the pigment include carbon black, etc. Examples of the ion trapping agent include hydrotalcites, bismuth hydroxide, etc.
[0056] (Resin layer) The resin layer contained in the laminate of the present disclosure is a cured product of the above-mentioned thermosetting composition. The glass transition temperature Tg of this cured product may be 130°C or higher, 150°C or higher, 170°C or higher, 190°C or higher, or 250°C or lower. The higher the glass transition temperature of the cured product, the better the adhesion to metal members in a high temperature environment. The glass transition temperature of the cured product is measured in accordance with the method described in JIS K7121:2012.
[0057] The cured product of the thermosetting composition of the present disclosure may have a chlorine content of 1000 ppm or less, 900 ppm or less, 800 ppm or less, or 500 ppm or less. The lower the chlorine content of the cured product, the better the adhesion to metal members in a high-temperature environment. Therefore, the lower limit of the chlorine content in the cured product is not particularly limited, but for example, the chlorine content may be more than 0 and may be 50 ppm or more. The chlorine content of the cured product is measured by X-ray fluorescence analysis (XRF). In the present disclosure, the chlorine contained in the cured product of the thermosetting composition is mainly derived from the chlorine in the thermosetting composition as a raw material or chlorine mixed in during the curing process. By reducing the chlorine in the thermosetting composition and preventing the mixing of chlorine during the curing process, a cured product of the thermosetting composition having a chlorine content of 1000 ppm or less can be obtained.
[0058] The cured product of the thermosetting composition of the present disclosure may have a sulfur content of 1000 ppm or less, 900 ppm or less, 800 ppm or less, or 500 ppm or less. The lower the sulfur content of the cured product, the better the adhesion to metal members in a high-temperature environment. Therefore, the lower limit of the sulfur content in the cured product is not particularly limited, but for example, the sulfur content may be more than 0 and may be 50 ppm or more. The sulfur content of the cured product is measured by X-ray fluorescence analysis (XRF). In the present disclosure, the sulfur contained in the cured product of the thermosetting composition is mainly derived from the sulfur in the thermosetting composition as a raw material or the sulfur mixed in during the curing process. By reducing the sulfur in the thermosetting composition and preventing the mixing of sulfur during the curing process, a cured product of the thermosetting composition having a chlorine content of 1000 ppm or less can be obtained.
[0059] (Method of manufacturing laminate) The laminate of the present disclosure can be obtained by a manufacturing method including a step (A) of supplying the above-mentioned thermosetting composition to a metal member, a step (B) of curing the thermosetting composition supplied to the metal member to form a resin layer, and a step (C) of completely curing the formed resin layer. This manufacturing method may include a step (A1) of directly supplying the thermosetting composition to the surface of the metal member after placing the metal member in a mold, a step (B1) of curing the thermosetting composition in the mold by heating and pressurizing the mold containing the metal member and the thermosetting composition to form a resin layer directly laminated on the surface of the metal member, and a step (C1) of further heating the metal member and the resin layer to completely cure the resin layer. The heating and pressurizing conditions in the step (B1) can be appropriately adjusted depending on the composition of the thermosetting composition, etc., but the heating temperature may be 150 to 250°C, and the heating time may be 60 to 500 seconds. The heating conditions in step (C1) can be appropriately adjusted depending on the composition of the thermosetting composition, etc., but the heating temperature may be 100 to 250°C, the heating time may be 2 to 6 hours, or a step cure may be performed by combining different temperatures and times.
[0060] In the present disclosure, the thermosetting composition contains the above-mentioned thermosetting compound having an alicyclic epoxy group. Therefore, the method for producing a laminate may further include a step (C) of preparing a thermosetting composition by blending various additives such as a curing agent and a filler with the thermosetting compound before the step (A). A known kneading machine such as a kneader or a Banbury mixer can be used to prepare the thermosetting composition.
[0061] In one embodiment, the manufacturing method may further include a step (D) of removing an oxide film from the surface of the metal member before the step (A). For example, the surface of the metal member is successively contacted with acetone and alcohol, and then ultrasonically cleaned in pure water to remove oil from the surface of the metal member. The metal member from which the oil has been removed is contacted with an acid aqueous solution to remove the oxide film from the surface of the metal member.
[0062] Examples of the alcohol include isopropyl alcohol (IPA), ethanol, etc. Examples of the acid in the aqueous acid solution include sulfuric acid, nitric acid, hydrochloric acid, etc. EXAMPLES
[0063] The effects of the present disclosure will be clarified by the following examples, but the present disclosure should not be interpreted as being limited based on the description of the examples. The details of the compounds used in the examples are as follows.
[0064] (thermosetting compound) Alicyclic epoxy group-containing compound 1: Celloxide 2021 (CEL2021P) manufactured by Daicel Corporation, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (formula (1-1) below), epoxy equivalent 130g / eq, chlorine content (below detection limit)
[0065] [ka]
[0066] Alicyclic epoxy group-containing compound 2: Celloxide 8010 (CEL8010) manufactured by Daicel Corporation, epoxy equivalent 100g / eq, chlorine content (below detection limit) Alicyclic epoxy group-containing compound 3: Celloxide 2081 (CEL2081) manufactured by Daicel Corporation, epoxy equivalent 200g / eq, chlorine content (below detection limit) Alicyclic epoxy group-containing compound 3: 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (above formula (1-1)) manufactured by Daicel Corporation, epoxy equivalent 130g / eq, chlorine content 580ppm Alicyclic epoxy group-containing compound 4: 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (above formula (1-1)) manufactured by Daicel Corporation, epoxy equivalent 130g / eq, chlorine content 1000ppm Glycidyl group-containing compound: YD-128 manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., bisphenol A diglycidyl ether (formula (3) below), epoxy equivalent 190 g / eq, chlorine content 1700 ppm Biphenyl skeleton-containing epoxy compound: Showa Denko Co., Ltd. product name CEL-420HFA
[0067] [ka]
[0068] (hardening agent) Acid anhydride hardener: Daicel's B0954B (4-methylphthalic anhydride:phthalic anhydride mixture (mixture ratio 7:3), contains 1% phosphorus-based hardening accelerator and 2% ethylene glycol)
[0069] (Filler) Silica: Denka FB-5FDC, 20μm cut Carbon black: MA100, φ24nm, manufactured by Mitsubishi Chemical Corporation
[0070] [Example 1] (Preparation of Thermosetting Composition) Alicyclic epoxy group-containing compound 1 (CEL2021P mentioned above), acid anhydride curing agent (B0954B mentioned above), silica (FB-5FDC mentioned above) and carbon black (MA100 mentioned above) were put into a kneader (Thinky Corporation) and kneaded at room temperature at 2000 rpm for 10 minutes to obtain a thermosetting composition (1). The amount of acid anhydride curing agent was 115 parts by weight relative to 100 parts by weight of alicyclic epoxy group-containing compound 1. The amounts of carbon black and silica in the thermosetting composition (1) were 0.2% by weight and 71.5% by weight, respectively.
[0071] (Manufacture of laminates) A Cu substrate (C1020-1 / 2H, thickness 2.0 mm) was prepared as a metal member. This Cu substrate was set in a mold, and the thermosetting composition (1) was injected onto the surface of the Cu substrate and compression molded (175°C, 3 MPa, 300 seconds), and then heated in an oven at 100°C for 2 hours, and then heated at 150°C for 2 hours (step cure), thereby completely curing the thermosetting composition (1). Thereafter, the laminate in which the cured product (resin layer) of the thermosetting composition (1) was laminated on the Cu substrate was taken out of the mold and cut to obtain a package with outer dimensions of 12.5 mm x 12.5 mm and thickness of 3.3 mm. This cured product had a glass transition temperature Tg of 187°C, a linear expansion coefficient of α1: 84.3, α2: 155.3, and a flexural modulus of 3279 MPa.
[0072] [Example 2] A laminate of Example 2 was obtained in the same manner as in Example 1, except that an alicyclic epoxy group-containing compound 2 (the above-mentioned CEL8010) was used as the thermosetting compound and the amount of the curing agent was 150 parts by weight per 100 parts by weight of the alicyclic epoxy group-containing compound 2. The cured product contained in the laminate of Example 2 had a glass transition temperature Tg of 235°C, a linear expansion coefficient α of 1:81, and a flexural modulus of 3272 MPa.
[0073] [Comparative Example 1] A laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that a glycidyl group-containing compound (the above-mentioned YD-128) was used as the thermosetting compound and the amount of the curing agent was 80 parts by weight per 100 parts by weight of the glycidyl group-containing compound. The cured product contained in the laminate of Comparative Example 1 had a glass transition temperature Tg of 125°C, linear expansion coefficients of α1:72 and α2:184, and a flexural modulus of 2828 MPa.
[0074] [Comparative Example 2] Except for using a biphenyl skeleton-containing epoxy compound (the above-mentioned CEL-420HFA) as the thermosetting compound and changing the amount of the curing agent to 80 parts by weight per 100 parts by weight of the biphenyl skeleton-containing epoxy compound, a laminate of Comparative Example 2 was obtained in the same manner as in Example 1. The cured product contained in the laminate of Comparative Example 2 had a glass transition temperature Tg of 270°C, a linear expansion coefficient of α1:16, α2:95, and a flexural modulus of 13.5 GPa.
[0075] [Reference example 1] Except for forming a copper diffusion prevention film (4-aminothiophenol) on the surface of the Cu substrate before compression molding, the laminate of Reference Example 1 was obtained in the same manner as Comparative Example 1. The physical properties of the cured product contained in the laminate of Reference Example 1 are similar to those of Comparative Example 1.
[0076] (High temperature reliability test) The packages produced in the Examples, Comparative Examples and Reference Examples were stored in an oven at 200°C, and the change over time in the adhesive strength (shear strength) between the resin layer and the metal member (Cu substrate) was examined. The storage times were 0 hours, 240 hours, 500 hours and 1000 hours. In addition, X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (ATR-FTIR) were performed on the resin layer at each storage time. Details of each measurement method are as follows. In the following measurement methods, "sample" can be appropriately read as "laminate", "resin layer", etc.
[0077] (Shear strength measurement) The resin layer of the laminate was partially removed by opening the package with a laser, and four resin layers of a prismatic shape (4 mm x 4 mm, height 1.3 mm) were formed on the Cu substrate as the cured product of the thermosetting composition (1). Then, for each of the prismatic resin layers, the bond strength (shear strength) between the cured product of the thermosetting composition and the Cu substrate was measured using a bond tester (Dage-4000 manufactured by Nordonson Dage). The measurement conditions were as follows. The shear strength was measured for the four resin layers to obtain the average value (arithmetic mean value) and standard deviation. Using this average value, the ratio (%) of the shear strength after each storage time to the shear strength before storage (0 hours) was calculated. The obtained results are shown in the table below as "strength %". Distance between head and Cu substrate: 200 μm Head speed: 50μm / s
[0078] [Table 1]
[0079] [Table 2]
[0080] [Table 3]
[0081] [Table 4]
[0082] (X-ray photoelectron spectroscopy (XPS)) After the above-mentioned shear strength measurement, the resin layer peeled off from the Cu substrate was used as a sample for XPS measurement. Specifically, argon ions (Ar +), and an acceleration voltage of 2 kV, and then the elemental composition of copper (Cu), oxygen (O) and carbon (C) was analyzed by XPS measurement. Furthermore, by repeating sputtering and XPS measurement, a depth profile of the elemental composition of the resin layer up to a depth of 100 nm from the fracture surface (bonding surface with the Cu substrate) was obtained. An X-ray photoelectron spectrometer (Ulvac-phi) was used for the measurement. The obtained results are shown in Figure 1-4. In Figure 1-4, the horizontal axis is the depth (nm) from the fracture surface, and the vertical axis is the atomic concentration (atoic%). 1A is an XPS profile of Example 1 before the high-temperature treatment (storage time 0 hours), FIG. 1B is an XPS profile of Example 1 after the high-temperature treatment (storage time 1000 hours), FIG. 2A is an XPS profile of Example 2 before the high-temperature treatment (storage time 0 hours), FIG. 2B is an XPS profile of Example 2 after the high-temperature treatment (storage time 1000 hours), FIG. 3A is an XPS profile of Comparative Example 1 before the high-temperature treatment (storage time 0 hours), FIG. 3B is an XPS profile of Comparative Example 1 after the high-temperature treatment (storage time 1000 hours), FIG. 4A is an XPS profile of Reference Example 1 before the high-temperature treatment (storage time 0 hours), and FIG. 4B is an XPS profile of Reference Example 1 after the high-temperature treatment (storage time 1000 hours).
[0083] (Fourier transform infrared spectroscopy (ATR-FTIR)) After the above-mentioned shear strength measurement, the resin layer peeled off from the Cu substrate was used as a sample for ATR-FTIR measurement. Specifically, a Fourier transform infrared spectrometer (manufactured by PerkinElmer) was used to measure the fracture surface of the resin layer (the adhesive surface with the Cu substrate) by the ATR method, and the infrared absorption spectrum (wavelength 600 to 4000 cm -1 ) was obtained. The measurement depth by ATR-FTIR is about 1 μm. The obtained results are shown in FIGS. 5-8. FIG. 5 is an infrared absorption spectrum obtained for Example 1, FIG. 6 is an infrared absorption spectrum obtained for Example 2, FIG. 7 is an infrared absorption spectrum obtained for Comparative Example 1, and FIG. 8 is an infrared absorption spectrum obtained for Reference Example 1.
[0084] (X-ray fluorescence analysis (XRF)) After the above-mentioned shear strength measurement, the resin layer peeled off from the Cu substrate was used as a sample for XRF measurement. Specifically, an X-ray fluorescence spectrometer (manufactured by Rigaku under the trade name "ZSX100e") was used to perform elemental analysis of chlorine (Cl) and sulfur (S) in the resin layer before high-temperature treatment (storage time 0 hours) for Examples 1 and 2 and Comparative Examples 1 and 2, to determine the chlorine content (ppm) and sulfur content (ppm). The results are shown in the table below. The symbol "-" in the table indicates that the content is below the detection limit of the X-ray fluorescence spectrometer, 100 ppm or less.
[0085] [Table 5]
[0086] (Transmission Electron Microscopy / Energy Dispersive X-ray Spectroscopy (TEM / EDS)) After the above-mentioned shear strength measurement, the cross sections of the samples of Comparative Example 1 and Comparative Example 2 were observed using a transmission electron microscope (trade name "JEM-ARM200F" manufactured by JEOL), and elemental analysis was performed on copper (Cu), sulfur (S) and chlorine (Cl) in the resin layer. The results obtained for Comparative Examples 1 and 2 after high-temperature treatment (storage time 1000 hours) are shown in Figures 9 and 10, respectively. Figures 9A and 9B are TEM images of Comparative Example 1 at different magnifications, Figure 9C is an EDS image of copper (Cu) in Figure 9B, Figure 9D is an EDS image of sulfur (S) in Figure 9B, and Figure 9E is an EDS image of chlorine (Cl) in Figure 9B. Figure 10A is a TEM image of Comparative Example 2, Figure 10B is an EDS image of copper (Cu) in Figure 10A, and Figure 10C is an EDS image of sulfur (S) in Figure 10A. The magnification of each image is according to the scale attached to the image.
[0087] (summary) As shown in Figures 1 and 2, in the laminate of the embodiment, the metal content after 1000 hours at 200 ° C. was 1 atomic % or less at a depth of 100 nm from the contact surface with the metal member, and as shown in Table 1-2, the shear strength of the bonding surface after 240 hours at 200 ° C. was 50% or more of the initial strength. In contrast, in the laminate of the comparative example, the metal content after 1000 hours at 200 ° C. was more than 10 atomic % at a depth of 100 nm from the contact surface with the metal member, and the closer to the contact surface, the higher the metal content. Also, as shown in Table 3, in the laminate of the comparative example, the shear strength of the bonding surface after 240 hours at 200 ° C. was reduced to 3% of the initial strength. From these results, it can be confirmed that the metal content in the vicinity of the bonding surface with the metal member is a factor in the reduction of adhesive strength (shear strength).
[0088] As shown in Fig. 4, in the reference laminate having a metal diffusion prevention film between the resin layer and the metal member, the metal content after 1000 hours at 200°C was 5 atomic% or less at a depth of 100 nm from the contact surface with the metal member, and as shown in Table 4, the shear strength of the bonding surface after 240 hours at 200°C was 21% of the initial strength. Comparing Fig. 3 with Table 3, it can be seen that the increase in the metal content in the resin, which is the cause of the decrease in adhesive strength, is due to the diffusion of metal elements from the metal member to the resin layer in a high-temperature environment.
[0089] As shown in Figures 5 and 6, in the laminate of the Example, there is no change in the infrared absorption spectrum even after 1000 hours at 200°C, and it is understood that there is no deterioration of the resin layer. In contrast, in the laminate of the Comparative Example, as shown in Figure 7, a decrease in the infrared absorption peak was confirmed after 1000 hours at 200°C. This is presumably due to a decrease in the amount of functional groups accompanying deterioration of the cured product constituting the resin layer.
[0090] Comparing FIG. 7 with Table 3, in the laminate of the comparative example, the shear strength decreased to 0% of the initial strength even though there was no change in the infrared absorption spectrum after 500 hours at 200° C. Also, as shown in FIG. 8, in the laminate of the reference example in which the metal content in the resin layer was not increased by the metal diffusion prevention film, the shear strength decreased to 0% of the initial strength even though there was no change in the infrared absorption spectrum after 1000 hours at 200° C. This is thought to be because ATR-FTIR measures the resin at a depth of about 1 μm from the contact surface with the metal member, and therefore could not detect deterioration of the resin near the contact surface with the metal member (at a depth of about 100 nm).
[0091] As shown in Table 5, chlorine and / or sulfur were detected in the resin layer in Comparative Examples 1 and 2, but both chlorine and sulfur were below the detection limit in Examples 1 and 2. From this result, it can be seen that the diffusion of copper from the Cu substrate to the resin layer is affected by the content of impurity elements such as chlorine and sulfur contained in the resin. The surface of copper is generally covered with an oxide film under atmospheric pressure. This oxide film is copper oxide. When copper diffuses into the resin layer in a high-temperature environment, it is necessary that copper is ionized from the crystal structure of copper oxide, or copper directly below the oxide film passes through the crystal structure of the oxide film and is ionized. It is considered that elements such as sulfur and chlorine contained in the resin react with the oxide film to promote the ionization of copper constituting the oxide film. Similarly, it is considered that copper directly below the oxide film is easily able to pass through. When the content of chlorine or sulfur is low, the amount of copper passing through due to the reaction is small, and therefore it is considered that the diffusion of copper into the resin layer due to the ionization of copper is suppressed.
[0092] 9 and 10, chlorine and / or sulfur were observed in the same positions as copper that had diffused into the resin layer. It is believed that copper reacted with chlorine and / or sulfur in a high-temperature environment and diffused into the resin.
[0093] According to the technology of the present disclosure, which focuses on the metal content in the vicinity of the contact surface with the metal member, it is possible to obtain a laminate in which deterioration of the resin in that region is suppressed. As a result, peeling between the resin layer and the metal member in a high-temperature environment is reduced, thereby improving the high-temperature reliability of the laminate.
[0094] As described above, the laminates of the examples were evaluated higher than the laminates of the comparative examples. From these evaluation results, the superiority of the present disclosure is clear.
[0095] [Disclosure items] Each of the following sections discloses a preferred embodiment.
[0096] [Item 1] A metal member and a resin layer laminated on the metal member, The resin layer is a cured product of a thermosetting composition, The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group, The resin layer is a laminate in which the metal content after 1000 hours at 200° C., as determined by the following measurement method, is 1 atomic % or less at a depth of 100 nm from the contact surface with the metal member. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction on the resin layer peeled off from the metal member using an X-ray photoelectron spectroscopy device (XPS) to measure the number of atoms of metal elements, carbon and oxygen, and the ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).)
[0097] [Item 2] The metal member is made of copper, Item 2. The laminate according to item 1, wherein the resin layer has a copper content of 1 atomic % or less at a depth of 100 nm from the contact surface with the metal member after 1000 hours at 200° C., as determined by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction on the resin layer peeled off from the metal member using an X-ray photoelectron spectroscopy device (XPS) to measure the number of copper, carbon and oxygen atoms, and the ratio of the number of copper atoms to the total number of carbon, oxygen and copper atoms at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the copper content (atomic %).)
[0098] [Item 3] 3. The laminate according to item 1 or 2, wherein a shear strength of a joint surface between the resin layer and the metal member after storage at a temperature of 200° C. for 240 hours is 50% or more of the shear strength before the storage.
[0099] [Item 4] 4. The laminate according to any one of items 1 to 3, wherein the thermosetting compound has a chlorine content of 1000 ppm or less.
[0100] [Item 5] 5. The laminate according to any one of items 1 to 4, wherein the thermosetting compound has an epoxy equivalent of 200 g / eq or less.
[0101] [Item 6] 6. The laminate according to any one of items 1 to 5, wherein the thermosetting compound is a compound represented by the following formula (1): [ka] (In formula (1), X represents a single bond or a linking group.)
[0102] [Item 7] 7. The laminate according to any one of the preceding items, wherein the thermosetting composition further comprises a curing agent.
[0103] [Item 8] 8. The laminate according to any one of items 1 to 7, wherein the glass transition temperature Tg of the cured product of the thermosetting composition is 130° C. or higher and 250° C. or lower.
[0104] [Item 9] 9. The laminate according to any one of items 1 to 8, wherein the cured product of the thermosetting composition has a chlorine content of 1000 ppm or less.
[0105] [Item 10] 10. The laminate according to any one of items 1 to 9, wherein the cured product of the thermosetting composition has a sulfur content of 1000 ppm or less.
[0106] [Item 11] 11. The laminate according to any one of items 1 to 10, wherein the metal member is a component of a semiconductor device.
[0107] [Item 12] supplying the thermosetting composition to the metal member; and curing the thermosetting composition supplied to the metal member to form the resin layer.
[0108] [Item 13] A thermosetting composition for use in producing a laminate, comprising: The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group, The cured product of the thermosetting composition has a chlorine content of 1000 ppm or less and a sulfur content of 1000 ppm or less, The cured product of the above thermosetting composition has a metal content of 1 atomic % or less at a depth of 100 nm from a contact surface with a metal member after 1,000 hours at 200°C, as measured by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) made of a cured product of a thermosetting composition laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction of the resin layer peeled off from the metal member using an X-ray photoelectron spectrometer (XPS) to measure the number of atoms of metal elements, carbon and oxygen, and the ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).)
[0109] [Item 14] Item 14. The thermosetting composition according to item 13, wherein the laminate is a semiconductor device. [Industrial Applicability]
[0110] The techniques described above can be applied not only to the semiconductor field, but also to the manufacture of other products obtained by joining or adhering metal members and resins.
Claims
1. A metal member and a resin layer laminated on the metal member, the resin layer is a cured product of a thermosetting composition, The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group, The resin layer has a metal content of 1 atomic % or less at a depth of 100 nm from the contact surface with the metal member after 1000 hours at 200° C., as measured by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction of the resin layer peeled off from the metal member using an X-ray photoelectron spectrometer (XPS) to measure the number of atoms of metal elements, carbon and oxygen. The ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).)
2. The metal member is made of copper, 2. The laminate according to claim 1, wherein the resin layer has a copper content of 1 atomic % or less at a depth of 100 nm from the contact surface with the metal member after 1000 hours at 200° C. as measured by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction of the resin layer peeled off from the metal member using an X-ray photoelectron spectrometer (XPS) to measure the number of copper, carbon and oxygen atoms, and the ratio of the number of copper atoms to the total number of carbon, oxygen and copper atoms at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the copper content (atomic %).)
3. 2. The laminate according to claim 1, wherein a shear strength of a joint surface between the resin layer and the metal member after storage at a temperature of 200° C. for 240 hours is 50% or more of the shear strength before the storage.
4. The laminate according to claim 1 , wherein the thermosetting compound has a chlorine content of 1000 ppm or less.
5. The laminate according to claim 1 , wherein the thermosetting compound has an epoxy equivalent of 200 g / eq or less.
6. The laminate according to claim 1 , wherein the thermosetting compound is a compound represented by the following formula (1): 【Chemistry 1】 (In formula (1), X represents a single bond or a linking group.)
7. The laminate of claim 1 , wherein the thermosetting composition further comprises a curing agent.
8. The laminate according to claim 1 , wherein the glass transition temperature Tg of the cured product of the thermosetting composition is 130° C. or higher and 250° C. or lower.
9. The laminate according to claim 1 , wherein the cured product of the thermosetting composition has a chlorine content of 1000 ppm or less.
10. The laminate according to claim 1 , wherein the cured product of the thermosetting composition has a sulfur content of 1000 ppm or less.
11. 2. The laminate according to claim 1, wherein the metal member is a component of a semiconductor device.
12. supplying the thermosetting composition to the metal member; The method for producing a laminate according to claim 1 , further comprising the step of curing the thermosetting composition supplied to the metal member to form the resin layer.
13. A thermosetting composition for use in producing a laminate, comprising: The thermosetting composition contains a thermosetting compound having an alicyclic epoxy group, A cured product of the thermosetting composition has a chlorine content of 1000 ppm or less and a sulfur content of 1000 ppm or less, The cured product of the above thermosetting composition has a metal content of 1 atomic % or less at a depth of 100 nm from a contact surface with a metal member after 1,000 hours at 200°C, as measured by the following measurement method. (Measuring method: A laminate having a resin layer (thickness 1.3 mm) made of a cured product of a thermosetting composition laminated on a metal member is prepared by compression molding (temperature 175°C, pressure 3 MPa), and this laminate is stored at a temperature of 200°C for 1000 hours. After that, elemental analysis is performed in the depth direction of the resin layer peeled off from the metal member using an X-ray photoelectron spectrometer (XPS) to measure the number of atoms of metal elements, carbon and oxygen. The ratio of the number of atoms of metal elements to the total number of atoms of carbon, oxygen and metal elements at a depth of 100 nm from the contact surface of this resin layer with the metal member is calculated as the metal content (atomic %).)
14. The thermosetting composition of claim 13, wherein the laminate is a semiconductor device.
